Percutaneous treatment with the Örmeci technique for hydatid disease located in the spleen: Single center experience for twenty six years - Örmeci, Necati; Kalkan, Çağdaş; Karakaya, Fatih; Erden, Ayşe; Köse, Kenan Serdal; Tüzün, Ali Emrehan; Deda, Xheni (Turkish Journal of Gastroenterology, 2018)
Abstract Background/Aims: Hydatid disease remains an important global socioeconomic health problem, particularly in the endemic areas. Although half of the patients show no symptoms, hydatid cysts should be treated because of their fatal complications. The aim of this study is to present the long-term results of percutaneous treatment of hydatid disease using the Örmeci technique. Materials and Methods: Forty-nine patients with 54 cystic lesions were diagnosed with hydatid disease. Twenty-seven of the 54 hydatid cysts located in the spleen were punctured with a 22-gauge Chiba needle through the parenchyma of the spleen under sonographic guidance as a one-step procedure. For every 1 cm of the long diameter of the cyst lesion, 3 cc of fluid from the cysts was aspirated. For each centimeter of the long diameter, 2 cc of pure alcohol (96%) and 1 cc of polidocanol (1%) were injected into the cysts. Five out of 27 patients did not participate in the follow-up. Results: The 22 patients who were treated using the percutaneous Örmeci technique were followed up for a mean±SD (median) of 50.32±65.30 (26.00) months (minimum 4 and maximum 298 months). All patients except one were successfully treated. No deaths or major complications were noted. Seven patients experienced minor complications. Conclusion: Percutaneous treatment with the Örmeci technique is a safe, effective, cheap, and reliable method that does not interfere with splenic functions, and this outpatient procedure should be the method of choice for a surgery alternative. Cite this article as: Örmeci N, Kalkan Ç, Karakaya F, et al. Percutaneous treatment with the Örmeci technique for hydatid disease located in the spleen: Single center experience for twenty six years. Turk J Gastroenterol 2018; 29: 566-73